Socioeconomic and Demographic Variables Associated with Self- Reported Domestic Violence During the "Stay At Home!" Mandate: A Cross-Sectional Study with a Sample of a University Community - Baptista, Cremildo João; Santos, Josenaide Engracia dos; Galassi, Andrea Donatti (O Mundo da Saúde, 2023)
This study aimed to estimate the frequency and identify socioeconomic and demographic variables associated with self-reporting of domestic violence during social distancing measures resulting from the COVID-19 pandemic in a university community. This is a cross-sectional study with an online convenience sample. Students, administrative assistants, and professors were eligible for the study. Participation consisted of answering a self-administered questionnaire with sociodemographic questions and experiences of the pandemic. Absolute and relative frequencies were calculated, and the proportions of categorical variables were compared using the chi-square test. Odds ratios were estimated via logistic regression to identify factors associated with self-reporting of domestic violence during social distancing. From July to August 2020, 2,629 participants responded to the questionnaire. Most were female (57%), single (67%), white (55%), and were up to 29 years of age (62%). Self-reported domestic violence was associated with elementary/high school education (AOR.: 2.80; 95% CI: 1.60 – 5.50), undergraduate level (AOR.: 2.20; 95% CI: 1.20 – 4 .40), female sex (AOR.: 1.60; 95% CI: 1.20 – 2.20), and single status (AOR.: 1.60; 95% CI: 1.10 – 2.40). Combating violence, especially against women, single and low educated people, must be constructed from intersectoral and networked basis, involving liberating actions, care, protection, psychosocial assistance, and professional training.